ANALISIS KOMPONEN ASAM LEMAK DAN MINERAL (Ca, Mg, Fe, Zn) IKAN KAKAP PUTIH (Lates calcalifer) - Nazudin Nazudin; Hernina Wattimena (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
ABSTRACT The analysis of fatty acid component and mineral composition (Ca, Mg, Fe, Zn) of white snapper fish (Lates calclifer) had been done. Flesh of white snapper fish (Lates calclifer) was extracted with petroleum benzene and obtained 6.06% of oil. Oil fish was transesterified by using BF3 – methanol 20%. The result of transesterification was analysed by using and GC-MC obtained nine fatty acid component, those were myristic acid methyl ester 5.94%; pentadecanoic acid methyl ester 1,58%; palmitoleic acid methyl ester 8.73; palmi acid methyl ester 17.69; Margarate acid methyl ester 1.96%; linoleic acid methyl ester 1.56%; oleic acid methyl ester 15.83%; streaic acid methyl ester 10.41%; aracidonic acid methyl ester 5.26%. the result of minerals composition analysis used atom absorption spectrophotometer (ASS) showed that the content of calcium (Ca), Magnesium (Mg), ferrum (Fe), zinc (Zn), were 51,1 mg/kg; 574 mg/kg; 65 mg/kg; and 10,8 mg/kg, respectively. Oil of white snapper fish (Lates calcalifer) contains esensial fatty acid that is benefit to humans body. In the another hand, it also contains mineral content which is enough that it is goof to be consumend by the people.